Control analysis of the dependence of Escherichia coli physiology on the H(+)-ATPase. - Jensen, P R (1993)
The H(+)-ATPase plays a central role in Escherichia coli free-energy transduction and hence in E. coli physiology. We here investigate the extent to which this enzyme also controls the growth rate, growth yield, and respiratory rate of E. coli. We modulate the expression of the atp operon and determine the effect on said properties. When quantified in terms of control coefficients, we find that, in the wild-type cell growing on glucose in minimal medium, this key enzyme (H(+)-ATPase) exerts virtually no control on growth rate (magnitude of C < 0.01), a minor positive control on growth yield (C = 0.15), and a small but negative control on respiration rate (C = -0.25). The control the enzyme exerts on the consumption rate of the carbon and free-energy substrate is negative (C = -0.15). We also studied how the control coefficients themselves vary with the expression of the atp operon. As the level of expression of the atp operon was reduced, the control exerted by the H(+)-ATPase on growth rate and growth yield increased slightly; the control on growth rate passed through a maximum (C = 0.1) and disappeared when the atp operon was not expressed at all, reflecting that with this substrate there are alternative routes for ATP synthesis. At elevated levels of the H(+)-ATPase compared to the wild type, the control exerted by the enzyme on growth rate became negative. The evolutionary context of the absence of control by the atp operon on growth rate is discussed.